Pengaruh Frekuensi Pemberian Pakan Alami Cacing Sutra (Tubifex sp.) terhadap Pertumbuhan dan Kelangsungan Hidup Larva Ikan Lele (Clarias sp.) - Agnes Denni Simanullang; Syammaun Usman (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Catfish (Clarias sp.) is one of the fresh water species that is economical and one of the main comodities of aquaculture in Indonesia. Fulfillment the increasing of needs of community required cultivation supported the availability of adequate larvae with efficiency of feed production cost with the right feeding frequencies. This research aims to know the influence of the frequency of natural feeding silk worm (Tubifex sp.) towards growth and survival of catfish larvae. The method used in this study was a complete randomized design (RAL) with three treatments and three replications, as follows: P1 (feeding frequency 3 times a day), P2 (feeding frequency 4 times a day) and P3 (feeding frequency 5 times a day). The result showed that the different feeding frequency treatment had a very significant effect on growth but did not significantly affect the survival of larvae of catfish. The best feeding frequency in increasing larval growth and survival of larvae is P3 (feeding frequency 5 times a day) treatment with larval length increase of 3.6 cm and weight increase of 0.928 g.Keywords : Larvae of Catfish, Silk Worm, Feeding Frequency, Growth, Survival